Skeletal muscles with antagonistic muscular actions: morphological, contractile and metabolic characteristics - de Freitas, Carlos Eduardo A.; Zambelli Freitas, Selma de Bastos; Lopes, Francis da Silva; Dal Pai-Silva, Maeli [UNESP]; Picarro, Ivan da Cruz (Soc Chilena Anatomia, 2009)
The muscles can perform the same function in a specific segment (muscles of fast and slow contraction), and at the same time be antagonistic in relation to muscular action (flexors or extensors). The present research aimed to study the morphology, frequency and metabolism of fiber types and the contractile characteristics of extensor and flexors muscles of rabbit. We studied muscles anterior tibialis (AT), flexor digitorum supeficialis (FDS), extensor digitorum longus (EDL) and posterior tibialis (PT). The muscles were submitted to the techniques HE, NADH-TR and myofibrillar ATPase. In EDL and PT extensor muscles, the frequencies of red (SO + FOG) and white fibers (FG) were 68.77% and 31.23% versus 58.87% and 41.13%, respectively. In the AT and FDS flexor muscles, these frequencies were 75.14% and 24.86% versus 73.89% and 26.11%, respectively. In extensor muscles, the percentage of slow contraction fibers was 8.05% in EDL and 9.74% in PT, and in fast contraction, 91.95% in EDL and 90.26% in PT. In flexors, the slow contraction frequencies were 12.35% in AT and 8.17% in FDS, and in fast contraction, 87.65% and 91.83%, respectively. Skeletal muscles with antagonistic muscular actions (flexors and extensors) the morphological, contractile and metabolic characteristics are identical.

Los músculos estriados esqueléticos pueden desempeñar la misma función en un segmento corporal específico (músculos decontracción rápida y lenta), y al mismo tiempo pueden ser antagonistas en relación a su acción muscular (flexores o extensores). El objetivo de esta investigación fue analizar la morfología, el metabolismo y la frecuencia de los tipos de fibras y las características contráctiles de músculos flexores y extensores del conejo. Fueron evaluados los músculos tibial anterior (TA), flexor superficial de los dedos (FDS), extensor largo de los dedos (EDL) y tibial posterior (TP). Los músculos fueron sometidos a las técnicas de Hematoxilina Eosina (HE), NADH-TR y ATPase miofibrilar. En los músculos extensores EDL y TP, las frecuencias de los tipos de fibras rojas (SO + FOG) y fibras blancas (FG) fueron de 68,77% y 31,23% versus 58,87% y 41,13%, respectivamente. En los músculos flexores TA y FDS estas frecuencias fueron 75,14% y 24,86% versus 73,89% y 26,11%, respectivamente. En los músculos extensores el porcentaje de fibras de contracción lenta fue 8,05% en el EDL y 9,74% en el TP; y las fibras de contracción rápida fue de 91,95% en el EDL y 90,26% en el TP. En los flexores la frecuencia de fibras de contracción lenta fue12,35% en el TA y 8,17% FSD, y las fibras de contracción rápida fue 87,65% y 91,83% respectivamente. Músculos esqueléticos con acción muscular antagónica (flexores y extensores) poseen características morfológicas, contráctiles y metabólicas idénticas.
Músculo esquelético con acción muscular antogonista: características metabólicas, contratiles y morfológicas
Keywords: Contractile ability; Metabolic; Morphologic; Skeletal muscle